2023
DOI: 10.2147/dmso.s379473
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tsRNA Contributor to Impaired Diabetic Wound Healing via High Glucose-Induced Endothelial Dysfunction

Abstract: Purpose Delayed skin healing in diabetic wounds is a major clinical problem. The tRNA-derived small RNAs (tsRNAs) were reported to be associated with diabetes. However, the role of tsRNAs in diabetic wound healing is unclear. Our study was designed to explore the tsRNA expression profile and mine key potential tsRNAs and their mechanism in diabetic wounds. Methods Skin tissues of patients with diabetic foot ulcers and healthy controls were subjected to small RNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nonetheless, a strong association between being overweight or obese and T2DM persists, with statistics from a UK study showing that over 80% of people with T2DM have a BMI ≥25 (23),and that in overweight individuals, a sustained increase in BMI leads to increased mortality from T2DM (24). Regrettably, there has been no progress in controlling overweight prevalence in the population over the last decade or so, even as the number of overweight individuals continues to rise and being overweight becomes nearly the population norm (8). In patients with T2DM with a BMI ≥15, appropriate weight loss significantly improves abnormally elevated blood glucose, lipids and blood pressure, enabling patients to minimize exposure to cardiovascular disease risk factors (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a strong association between being overweight or obese and T2DM persists, with statistics from a UK study showing that over 80% of people with T2DM have a BMI ≥25 (23),and that in overweight individuals, a sustained increase in BMI leads to increased mortality from T2DM (24). Regrettably, there has been no progress in controlling overweight prevalence in the population over the last decade or so, even as the number of overweight individuals continues to rise and being overweight becomes nearly the population norm (8). In patients with T2DM with a BMI ≥15, appropriate weight loss significantly improves abnormally elevated blood glucose, lipids and blood pressure, enabling patients to minimize exposure to cardiovascular disease risk factors (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some tsRNAs have been found to be involved in adipose differentiation, promoting the proliferation of preadipocytes or enhancing adipogenesis to mediate obesity (6,7). Other studies have identified tsRNA as a key factor in the pathogenesis of diabetes and its related diseases (8), and suggested that alterations in tsRNA may be closely related to the mechanism of pancreatic b-cell death (9). Yan et al also discovered that tsRNA may act as a new target in the treatment of diabetic foot ulcers by regulating Wnt signaling (10).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 depicts aberrant tsRNA expression patterns across ten different diseases, Figure 3 illustrates aberrant tsRNA expression patterns across ten distinct diseases, encompassing one cancer and nine non-cancerous conditions. These tsRNAs encompass a range of variants, including tRF-03357 in HGSOC, tRF-36-F900BY4D84KRIME, tRF-23-87R8WP9IY, and tRF-40-86J8WPMN1E8Y7Z2R in VV, tRF-Gly-CCC-039 in diabetic foot, tRF-Arg-ACG-007 and tRF-Ser-GCT-008 in diabetes, tRF-5014a in DCM, tsRNA-14783 in Keloid, tsRNA-04002 in IDD, tsRNA-21109 in SLE, tiRNA-Gly-GCC-002, tRF-Ala-AGC-010, tRF-Gln-CTG-005, and tRF-Leu-AAG-001 in LN, as well as tsRNA-1018, tsRNA-3045b, tsRNA-5021a, and tsRNA-1020 in ALI ( Yu et al, 2019 ; Zhang et al, 2019 ; Zhao Y. et al, 2022 ; Wang and Hu, 2022 ; Zhang et al, 2023 )[37373469][37287061][34464838][34923866][34811808][37259935].…”
Section: Exploring Mapk-related Tsrnas In Disease: Identification Exp...mentioning
confidence: 99%
“…A total of 55 differentially expressed tsRNAs emerged from diabetic foot ulcer tissues, with tRF-Gly-CCC-039 showing high expression and correlation with the MAPK pathway through KEGG analysis. Elevated tRF-Gly-CCC-039 hindered proliferation, motility, angiogenic capacity, and expression of specific genes in human umbilical vein endothelial cells (HUVECs) ( Zhang et al, 2023 ). In diabetes, there is an upregulation in the expression of tRF-Arg-ACG-007, whereas the expression of tRF-Ser-GCT-008 is downregulated.…”
Section: Exploring Mapk-related Tsrnas In Disease: Identification Exp...mentioning
confidence: 99%
See 1 more Smart Citation